(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Monitoring of resource efficiency is a necessity of the market economy, which ensures scientific and technical development of raw materials, fuel and energy and other types of material resources in the economy, optimization of economic relations and proportions, strengthening of the economic regime, increasing the efficiency of the use of material resources., is a process of rationalization of use based on the introduction of progressive forms of management.